PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 LEMBANG JAYA KABUPATEN SOLOK - Widia Arif, Nova; K, Delsi; Harisman, Yulyanti (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research is motivated by the studentâs understanding of mathematical concepts are still low and studentâs are less interested in learning mathematics. This research aims to determine whether studentâs understanding of mathematical concepts by applying active learning strategies the power of two type better review than the studentâs understanding of mathematical concepts by applying conventional learning eighth grade students SMPN 3 Lembang Jaya Â academic year 2013/2014. This research is an experimental research, the design of randomized trials on the subject. The instrument used in this research is a test student understanding of mathematical concepts. Data analysis techniques are used to test the hypothesis is not a party with the help of MINITAB software. Based on the results of the analysis of the data found that both classes of normally distributed and homogeneous samples. Hypothesis test results obtained P - value = 0.025 is less than Î± = 0.05, then reject H0, so the hypothesis in this study received, so it can be concluded that the Studentâs understanding of mathematical concepts by applying active learning strategies the power of two better than the understanding of mathematical concepts studentâs by applying conventional learning eighth grade studentâs SMPN 3 Lembang Jaya academic year 2013/2014 .